1999
DOI: 10.1592/phco.19.3.249.30929
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Rifampin on Serum Amiodarone Concentrations in a Patient with Congenital Heart Disease

Abstract: A 33-year-old woman with congenital heart disease and atrial and ventricular arrhythmias, managed over the long term with an implantable cardioverter defibrillator, epicardial pacing system, and amiodarone, experienced an increase in palpitations and a shock from her defibrillator. Evaluation revealed decreases in amiodarone and desethylamiodarone serum concentrations from previous levels. Rifampin had been added to her therapy 5 weeks earlier. Increases in amiodarone and desethylamiodarone concentrations were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 14 publications
(9 reference statements)
1
5
0
1
Order By: Relevance
“…However, the ndings in the present paper are in accordance with the increase of MDEA (and AMI) clearance, when AMI and RIF were co-administered to a patient (Zarembski et al 1999). This drug interaction may be explained at least in part by the increase of the MDEA hydroxylase activity of RIF-induced enzyme(s).…”
supporting
confidence: 83%
“…However, the ndings in the present paper are in accordance with the increase of MDEA (and AMI) clearance, when AMI and RIF were co-administered to a patient (Zarembski et al 1999). This drug interaction may be explained at least in part by the increase of the MDEA hydroxylase activity of RIF-induced enzyme(s).…”
supporting
confidence: 83%
“…Interestingly, the authors found an increase in MDEA serum concentrations at the end of the study period [45]; however, whether this increase in metabolite serum concentrations with ongoing CYP3A4 induction would be sustained over longer observation periods remains to be seen given the possible role of 3A4 in the elimination of MDEA [15]. Another potent inducer of the P450 enzyme system, rifampin, has also been reported to lead to subtherapeutic amiodarone and MDEA serum concentrations and subsequent palpitations [46,47]. In both patient cases, amiodarone and MDEA levels returned to the therapeutic range and resolution of cardiac symptoms occurred after a dosage increase and/or the discontinuation of rifampin [46,47].…”
Section: Amiodarone and Antiretroviral Drug Interactionsmentioning
confidence: 99%
“…As far as the interaction of rifampicin with amiodarone is concerned, only single reports have demonstrated the effect of a 40% reduction in serum concentration of amiodarone and the resultant need to double the dose of an antiarrhythmic drug, which in turn was associated with a sudden increase in the concentration of amiodarone and its metabolites after the withdrawal of rifampicin [107].…”
Section: Rifampicinmentioning
confidence: 99%